Consider the following situation.

y = f(x)

P = f(y)

y is a function of x and P is a function of y.

Directly we cannot find any combination with P and x.

If we want (dP)/dx then;

`(dP)/dx = (dP)/dy*(dy)/dx`

` `

Since P is a function of y and y is a function of x we can evaluate (dP)/dx.

This is known as derivative of function of function.

`s(x) = sec^(-1)(x/2)`

Let;

`t = x/2`

`s(x) = sec^(-1)t`

`(ds(x))/dx = (ds(x))/dt*(dt)/dx`

`(ds(x))/dt = 1/(t*sqrt(^2-1)) = 1/(x/2*sqrt(x^2/4-1)) = 4/(xsqrt(4-x^2))`

`dt/dx = 1/2`

`(ds(x))/dx = 4/(xsqrt(4-x^2))*1/2 = 2/(xsqrt(4-x^2))`

`(ds(x))/dx = 2/(xsqrt(4-x^2))`

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.